ANALISIS KEUNTUNGAN INVESTASI di PASAR KEUANGAN PADA MASA PANDEMI COVID-19 - Lastri; Purba, Elvis Fresly; Sihotang, Jusmer; Tampubolon, Novianti (UNIKA Santo Thomas, 2022)
Investments can be made in various types in the financial market. Some of them are gold, stock, foreign exchange and deposit investments. However, during the COVID-19 pandemic, it is very difficult to make profitable and safe investments. This research was conducted to determine which types of investments are safe to do during the COVID-19 pandemic. By using the Kruskal Wallis test, which is non-parametric statistics, which is an alternative to the one-way ANOVA test that can be used if the sample is not normally distributed. From the results of the Kruskal Wallis Test, it was found that the most profitable type of investment in the financial market during the covid-19 pandemic was stock investment and the results of statistical tests showed that there were significant differences that were profitable from the types of investments in gold, stocks, and foreign exchange.